SOURCES REFLECTING UBAYDULLAH KHAN'S CAMPAIGNS IN KHORASAN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The Shaybanids created a large state in Central Asia in the 16th century through constant and intense struggles. Muhammad Shaybani Khan (1451–1510, reigned 1500–1510), Ubaydullah Khan (1487–1540, reigned 1533–1540), Kuchkinchi Khan (1452–1530, reigned 1510–1529) and the subsequent sultans of this dynasty were also intellectuals who were knowledgeable in science. There is a lot of information preserved in manuscripts and historical documents that they founded a number of higher educational institutions - madrasas, khanaqahs and libraries, especially in Turan, and patronized science and education. After Muhammad Shaybani Khan died in battle with Shah Ismail Safavi (1501-1524), his nephew Ubaydullah Khan united all the Shaybani sultans. He made several successful campaigns against Khorasan.